(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
This research is devoted to study the influence of different weight percent concerning to the additions of Ti and Cu on corrosion- fatigue and electrical properties of AA6061. The composite materials consist of different weight percentage of Ti (0.2, 0.4, and 0.6) and constant weight percentage of Cu (0.2) are fabricated by liquid metallurgy route technique.Attempts have been made to explore the impact of corrosive media on the fatigue behavior of AA6061 submerged for 80days in shat al Arab water. Constant and variable corrosion fatigue tests are performed under rotating bending loads and stress control at the stress ratio R= -1 and room temperature (RT). The results show the fatigue strength reduction due to corrosion without nano materials increases with the increasing of the testing cycles, but when adding nano material the fatigue strength reduction will be reduced with increasing the testing life. Furthermore the results of electrical tests show that increasing electrical conductivity and decrease of resistivity.